Memes in the Literature Studies Classroom - Yazell, Bryan; Wohlmann, Anita (Narrative Works, 2023)
This paper considers memes through the lens of riddles and discusses the generative or creative aspect of the meme format as applied in the classroom. In a literary studies course on cultural narratives, ranging from canonical to bestselling fiction, we critically discussed the genre-specific potential of memes, which students were encouraged to explore both intellectually and experientially. In addition, we asked students to create memes in their assessment of the course. The results were highly ambivalent, ranging from humor to seriousness, self-critique to critique of the course, panic (regarding the final exam) to playful exaggeration of said panic. This ambivalence, often accentuated by irony and excess, challenges any definitive understanding of the memes’ content and meaning. Rather than dismissing memes as a flawed, imprecise tool, this article examines them as riddled forms and hypothesizes that, due to their ambivalence, they may actually be closer to a student’s “truth.” The connection between memes and meaning-making is especially relevant to courses that, like the one in this article, foreground semantic ambiguity and an explorative habitus.